Finding Practical Approaches to Integrated Water Resources Management - John Butterworth (Water Alternatives, 2010)
Integrated Water Resources Management (IWRM) has often been interpreted and implemented in a way that is only really suited to countries with the most developed water infrastructures and management capacities. While sympathetic to many of the criticisms levelled at the IWRM concept and recognising the often disappointing levels of adoption, this paper and the series of papers it introduces identify some alternative ways forward in a developmental context that place more emphasis on the practical in-finding solutions to water scarcity. A range of lighter, more pragmatic and context-adapted approaches, strategies and entry points are illustrated with examples from projects and initiatives in mainly 'developing' countries. The authors argue that a more service-orientated (WASH, irrigation and ecosystem services), locally rooted and balanced approach to IWRM that better matches contexts and capacities should build on such strategies, in addition to the necessary but long-term policy reforms and river basin institution-building at higher levels. Examples in this set of papers not only show that the 'lighter', more opportunistic and incremental approach has potential as well as limitations but also await wider piloting and adoption.